A Comparison of Morphine Delivery in Neonatal Opioid Withdrawal - Brian Chisamore; Safaa Labana; Sandra Blitz; Alice Ordean (SAGE Publishing, 2016)
Current estimates of the prevalence of opioid withdrawal in newborns from the 2012 Better Outcomes Registry and Network Ontario reveal that more than 4 births per 1000 display recognizable symptoms of neonatal abstinence syndrome (NAS). With a growing consensus surrounding aspects of newborn opioid withdrawal care, clinicians might agree that all infants exposed to maternal opioids require supportive observation and care to ensure appropriate adaptation and growth in the newborn period and, likewise, that there exists a smaller percentage of newborns who require additional pharmacotherapy. However, due to the dearth of comparative studies of NAS tools, there remains a lack of evidence to support the use of a specific NAS method of scoring or treatment. Two types of NAS treatment protocols currently in use include a symptom-only versus weight-based protocols. Our Neonatal Intensive Care Unit (NICU) has used both models. A formal structured NAS tool and weight-based morphine delivery system began in our NICU in 1999. We audited all newborns with known exposure to maternal opioids in our NICU from the years 2000 to 2014. The Finnegan scoring tool was used throughout all years of the chart audit. Modifications made to the Finnegan scoring tool from the MOTHER study were adapted for use in our NICU at the same time as adopting the Johns Hopkins model of symptom-only based morphine delivery in 2006. The objective of this comparative study using a retrospective chart audit is to compare length of stay (LOS) and total accumulative morphine dose across these two morphine delivery protocols. Our audit revealed that there were a significantly higher proportion of newborns in the symptom-only model that received morphine and, perhaps accordingly, also had a significantly higher LOS compared to those in the weight-based model. Comparing only those infants who did receive morphine, the comparative total accumulative dose of morphine and LOS were not significantly different between the weight-based and symptom-only morphine delivery models.